2004
DOI: 10.1002/jrs.1139
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism and devitrification of nifedipine under controlled humidity: a combined FT‐Raman, IR and Raman microscopic investigation

Abstract: FT-Raman and FT-IR spectroscopy and Raman microscopy were employed to identify the structural characteristics of one amorphous and three crystalline phases of nifedipine, a common antihypertension drug of the 1,4-dihydropyridine family. A significant fraction of the nifedipine molecules in the glass are found to be frozen into metastable rotational conformations as a result of melt quenching. Moreover, the effect of relative humidity .RH = 20-80%/ on the onset and rate of crystallization was studied at 40 • C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
123
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(130 citation statements)
references
References 14 publications
6
123
1
Order By: Relevance
“…These band positions and assignments correspond to those reported [27] for α -nifedipine. The same peaks were observed in all the samples examined (especially that containing higher percentages of the drug).…”
Section: Spectroscopic Analysissupporting
confidence: 85%
See 1 more Smart Citation
“…These band positions and assignments correspond to those reported [27] for α -nifedipine. The same peaks were observed in all the samples examined (especially that containing higher percentages of the drug).…”
Section: Spectroscopic Analysissupporting
confidence: 85%
“…An intermolecular bond between one of the ester carbonyl and NH group of an adjacent nifedipine molecule is present in the solid state [27] . Similarly soluplus, among other claimed advantages, offers a variety of functional groups, such as the hydroxy groups at the end of the poly-oxyethylene chains, the carbonyl groups of the vinyl acetate moiety and the amide function of the caprolactam portion.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in-situ IR and Raman spectroscopy were used to study the recrystallisation of amorphous nifedipine in a controlled humidity cell at different relative humidities. [143] Increasing the relative humidity decreased the recrystallisation onset time. The authors concluded that in-situ IR and Raman microscopy are useful tools to examine environmental effects on the solid state of an API.…”
Section: Amorphous Formsmentioning
confidence: 98%
“…Paracetamol, ketoprofen, naproxen, ibuprofen [142] Amorphisation in polyethylene oxide matrices at high humidity Storage at high humidity (94% RH) in room temperature Raman spectroscopy Nifedipine [143] Recrystallisation of amorphous nifedipine via metastable b-form to a-nifedipine…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…24,29 Incorporating an optical microscope and motorized stage into the Raman instrument for spectroscopic chemical imaging by obtaining spectra for a defined 2-dimensional area with a resolution down to 1 μm 12 has further expanded Raman spectroscopy's utility in various structural and molecular investigations. These direct and quantitative Raman chemical imaging ( Figure 3) and mapping ( Figure 4) investigations include biomaterial nanotubes (providing a spatial resolution of~25 nm), 30 drug-polymer-controlled drug delivery systems, 31,32 solid-state polymorphic transformations, [33][34][35][36][37] and drug disposition research. 24,[38][39][40][41][42] The combination of scanning electron microscopy (SEM) and Raman spectroscopy has been applied in single-crystal hydration studies of carbamazepine, in the absence and presence of excipients, where it was demonstrated that defect structures were of greater importance in the initiation of the hydration process than the crystal face.…”
Section: Surface-enhanced Raman Spectroscopymentioning
confidence: 99%